Post herpetic neuralgia after acyclovir treatment - Mohamed, Abdul Hadi; Awang, Mohd Shukrimi; Abdullah, Nor Zamzila; Mat Nor, Mohd Basri (International Islamic University Malaysia, 2016)
Post Herpetic Neuralgia (PHN) is often diagnosed when pain persists in a dermatomal pattern weeks after the herpes zoster vesicular eruption has healed. There is a definite tendency for PHN to improve with time. There is no way of predicting who will recover. However, some reported that as many as 40% of patients with PHN will continue to have long-term problems because of incomplete or no pain despite the best treatments given. This retrospective series discussed the outcome of treatment of 3 patients with PHN, using acyclovir, Gabapentin and analgesics. Patients were treated by a single pain specialist in a conventional community pain practice. Therapies were given twice-monthly for 1-2 months, then less frequently until pain relief was optimized. Patients received a median of 7 treatments (range 4 - 11). Median baseline allodynia levels were reduced from 9 /10 (range 8 to 10) to 0/10 (range 0 to 6), intermittent shooting pain from 9/10 (range 8 to 10) to 0/10 (range 0 to 6). 1 of 3 patients (30%) was able to be weaned off pain medications. These data showed that there is variation in the response to treatment in patients suffering from PHN. The response ranged from a complete cure to unresponsive at all to the treatment given. There is no way of predicting who will fully recover.